VOLATILIZATION OF AMMONIA IN DIFFERENT TYPES OF BROILER LITTER - FREITAS, Leonardo Willian de; GARCIA, Rodrigo Garófallo; NÄÄS, Irenilza de Alencar; CALDARA, Fabiana Ribeiro; LIMA, Nilsa Duarte da Silva (Revista Brasileira de Engenharia de Biossistemas, 2011)
The present study was conducted to evaluate the use of different substrates for poultry litter and its influence on the weight gain of broilers. 2,332 day-old chicks, reared in conventional aviary divided into boxes of 4,5m² in density of 12 birds / m² were used. At 21, 28, 35 and 40 days of creation of the beds samples were collected for determination of dry matter (DM), pH, ammonia volatilization and temperature (° C). The experimental design was completely randomized, using six treatments (bed types: sugarcane bagasse, wood shavings, rice husk; Napier grass (Pennisetum purpureum), sugarcane bagasse (50%) + rice husk (50 %) and sugarcane bagasse (50%) + shavings (50%)) with five replicates (boxes) and 53 birds per pen. The shavings can be replaced by sugar cane bagasse, rice husk and its associations with the shavings. We do not recommend the use of crushed Napier grass.